Clinical spectrum of individuals with pathogenic NF1 missense variants affecting p.Met1149, p.Arg1276, and p.Lys1423: genotype–phenotype study in neurofibromatosis type 1. Issue 1 (26th October 2019) - Koczkowska, Magdalena; Callens, Tom; Chen, Yunjia; Gomes, Alicia; Hicks, Alesha D.; Sharp, Angela; Johns, Eric; Uhas, Kim Armfield; Armstrong, Linlea; Bosanko, Katherine Armstrong; Babovic‐Vuksanovic, Dusica; Baker, Laura; et al.
Abstract: We report 281 individuals carrying a pathogenic recurrent NF1 missense variant at p.Met1149, p.Arg1276, or p.Lys1423, representing three nontruncating NF1 hotspots in the University of Alabama at Birmingham (UAB) cohort, together identified in 1.8% of unrelated NF1 individuals. About 25% (95% confidence interval: 20.5–31.2%) of individuals heterozygous for a pathogenic NF1 p.Met1149, p.Arg1276, or p.Lys1423 missense variant had a Noonan‐like phenotype, which is significantly more compared with the "classic" NF1‐affected cohorts (all p < .0001). Furthermore, p.Arg1276 and p.Lys1423 pathogenic missense variants were associated with a high prevalence of cardiovascular abnormalities, including pulmonic stenosis (all p < .0001), while p.Arg1276 variants had a high prevalence of symptomatic spinal neurofibromas ( p < .0001) compared with "classic" NF1‐affected cohorts. However, p.Met1149‐positive individuals had a mild phenotype, characterized mainly by pigmentary manifestations without externally visible plexiform neurofibromas, symptomatic spinal neurofibromas or symptomatic optic pathway gliomas. As up to 0.4% of unrelated individuals in the UAB cohort carries a p.Met1149 missense variant, this finding will contribute to more accurate stratification of a significant number of NF1 individuals. Although clinically relevant genotype–phenotype correlations are rare in NF1, each affecting only a small percentage of individuals, together they impact counseling and management of a significant number of the NF1 population.